ANALISIS IMPLEMENTASI PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) DI NAGARI SILAYANG KECAMATAN MAPAT TUNGGUL SELATAN - Chintya Marsya Fitri; Zuwardi (CV. Adiba Aisha Amira, 2025)
Implementation of Self-Help Housing Stimulant Assistance (BSPS) in Nagari Silayang, Mapat nggul Selatan District. Self-help Housing Stimulant Assistance (BSPS) is a government facility in the form of stimulant assistance for building/improving the quality of houses given to low-income people. Low-Income Communities (MBR) are people who have limited purchasing power and therefore need government support to obtain livable housing. Self-help housing is houses built on the initiative and efforts of the community, either individually or in groups. The type of research used in this research is field research with a qualitative descriptive approach. The informants in this research were the Nagari Silayang officials and recipients of self-help housing stimulant assistance (BSPS) in Nagari Silayang. The data obtained in this research came from observations and interviews which were then analyzed using data reduction techniques, data presentation and drawing conclusions. The results of this research show that the implementation of the Self-Help Housing Stimulant Assistance Program in Nagari Silayang, Mapat nggul Selatan District is almost running optimally. The distribution of BSPS is almost completely on target, but in its implementation there is still a lack of public participation and awareness as well as a lack of knowledge about the BSPS program. Based on research that has been carried out, the process of distributing Self-Help Housing Stimulant Assistance is in accordance with the principles of Islamic economics, including the principles of justice, nubuwwah (prophetic qualities), and khilafah (government). The principle of justice is proven by statements from residents, including Mr.alih Nasrul. The nubuwwah principle here is proven by the Nagari officials who have carried out their duties in a trustworthy manner so that aid can be distributed to the right target. Meanwhile, the principle of the caliphate is proven by the role of nagari in ensuring that no irregularities occur in the process of distributing BSPS aid. For example, distributing aid in the form of materials, so as to prevent misuse of funds by aid recipients. Apart from that, the disbursement of funds in the form of materials means that workers can immediately use them for building houses.